A RETROSPECTIVE STUDY OF ADVERSE DRUG REACTION IN MULTIDRUG-RESISTANT TUBERCULOSIS PATIENTS AT TERTIARY CARE HOSPITAL - MISHRA, AMUL; MATHUR, SUNIL KUMAR; JAIN, SAURABH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to the analysis of different parameters including admission type, demographics, type of reaction, the seriousness of reaction, classification of organ system, drugs involved, action taken and outcome of reactions, causality assessment, severity assessment, and the preventability of ADRs for multidrug-resistant tuberculosis patients. Methods: This retrospective observational study was conducted during the period of September 2017 to June 2020 (34 months) at ADR Monitoring Centre, Department of Pharmacology, Jawaharlal Nehru Medical College, Ajmer, Rajasthan. All spontaneously reported ADRs were evaluated using various parameters such as type of reaction, causality assessment, preventability, and severity. Results: In the present study, 92 (9.29%) ADRs were reported in relation to 68 MDR-TB patients. The majority of ADRs were considered probable (73.92%), moderate (41.30%), and definitely preventable (42.39%) in nature. In our study, most of the suspected drug names were included: 23 (25%) pyrazinamide, followed by 22 (23.91%) kanamycin, 12 (13.04%) cycloserine, and 11 (11.96%) linezolid. The majority of ADRs were non-serious (67.39%) in nature. ADRs were most commonly reported, with 17 (18.48%) reporting ototoxicity and 17 (18.48%) reporting joint pain, followed by 4 (4.35%) reporting burning feet syndrome, 4 (4.35%) reporting generalized itching, and 4 (4.35%) reporting psychosis. Conclusion: Our study included 36 different types of suspected ADRs that were reported with multiple frequencies due to 16 categories of drugs and combinations of drugs. The majority of patients were recovering and recovered from concerns associated with ADR after necessary medical intervention and management. Our purpose is to rationale the use of medicines for drug safety as well as patient safety.